Pengaruh Kualitas Layanan dan Kepercayaan terhadap Kepuasan Pasien Dokter Gigi Muda di RSKGMP Prof. Dr. Moestopo - Mellynia; Abdul Aziz; Purwanti Aminingsih (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Patient satisfaction is a key indicator of hospital service quality. This study aims to analyze the influence of service quality and trust on patient satisfaction at RSGM Prof. Dr. Moestopo. A quantitative descriptive method with a cross-sectional design was employed. The sample consisted of 80 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results showed that service quality (p = 0.008) and patient trust (p = 0.000) significantly affected satisfaction. Simultaneously, both variables had a significant effect (p < 0.05) with an R² value of 0.718, indicating that 71.8% of patient satisfaction variation was explained by the two variables. Trust was identified as the most dominant factor. In conclusion, service quality and trust significantly influence patient satisfaction. Hospitals are advised to improve service quality through regular evaluation, service excellence training, and strengthening communication and digital feedback systems.